РОЗРАХУНОК ФУНКЦІЇ ЧИСЕЛЬНОСТІ НАСЕЛЕННЯ ДЛЯ ДИНАМІЧНОЇ МОДЕЛІ З НЕПЕРЕРВНИМ ЧАСОМ - Zagorodni, Yuriy; Voytenko, V. (Kamianets-Podilskyi National Ivan Ohiienko University, 2008)
In this article, we present an approach to identify functions in population process model with continuous-time age. The main consideration was given to functions identification of birth, mortality, migration and specific function “becoming mature”. Such functions could be defined analytically or by using specific numeric procedure. A numerical example is given to demonstrate the method, along with computer application to population analysis in Canada and Ukraine.